Physio-biochemical and antioxidative responses of different salt-sensitive sunflower (Helianthus annuus L.) genotypes - Hossain, Shakhawat (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2020)
Salinity is one of the important abiotic stresses affecting growth, photosynthesis, ion accumulation, and antioxidant defense systems in sunflower (Helianthus annuus L.). This study investigated the physio-biochemical and antioxidative responses in different salt-sensitive sunflower genotypes: GP-4030 and BARI Surzumukhi 2 as newly identified tolerant genotypes, PS-2 as sensitive and Hysan 33 as standard tolerant. Salt stresses caused higher reduction in relative water content (RWC), chlorophyll (Chl) content, K+ and K+/Na+ ratio, photosynthetic rate (pN), transpiration rate (E), stomatal conductance (gs), and intercellular CO2 concentration rate (Ci) in salt-sensitive genotype. This genotype had higher Na+, superoxide (O2.-), hydrogen peroxide (H2O2), lipid peroxidation (MDA) and proline (Pro) content than the tolerant genotypes. The tolerant genotypes maintained higher Pro content than the salt-sensitive genotypes under salt stress. All the tolerant genotypes had higher increment of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) activities under salinity (12 dS m-1) than the salt-sensitive genotype. Similarly, increment of ascorbate peroxidase (APX) and glutathione reductase (GR) activity was higher in the tolerant genotypes, but glutathione peroxidase (GPX) activity was higher in salt-sensitive genotype. However, both monodehydroascorbate reductase (MDHAR) and dehydroascorbate reductase (DHAR) activities decreased with salinity level. Glutathione S-transferase (GST) activity increased in all the genotypes under salinity and was higher in the tolerant genotypes. Higher accumulation of Pro, along with improved physiological and biochemical parameters in the tolerant genotypes, can confer tolerance by reducing oxidative damage through up-regulating antioxidant defense under salinity.